Analisis Implementasi Manajemen Risiko Berdasarkan SNI ISO 31000:2018 (Studi Kasus: Sparepart Personal Computer Second Jambi) - Prayetno Agustinus Sitanggang; Friska Artaria Sitanggang (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
Small & Medium-Sized Enterprises (SMES) Sparepart Personal Computer Second Jambi is an assembly and computer service. This study aims to analyze and manage risks to Sparepart Personal Computer Second Jambi based SNI ISO 31000: 2018. ISO 31000:2018 is an international standard application for auditing the application of risk management issued by The International Organization for Standardization (ISO), consisting of three elements: principle, framework, and process. The results of this study stated that there were any problems that had to be mitigated because they had high and moderate risks, which is comprised of eksternal risk is multiple business competitors, financial risk is unstable equipment and materials prices, K3 Risk is accidents at work,human resources risk is scarce manpower, and technical risk is blackouts.